2012
DOI: 10.1017/s0144686x12000062
|View full text |Cite
|
Sign up to set email alerts
|

Why are the oldest old less generous? Explanations for the unexpected age-related drop in charitable giving

Abstract: Previous research has demonstrated that the generally positive relationship between age and the presence of charitable giving becomes negative at the oldest ages. We investigate potential causes of this drop in charitable giving among the oldest old including changes in health, cognition, egocentric networks, religious attendance, and substitution of charitable bequest planning. A longitudinal analysis of data from the United States Health and Retirement Survey indicates that the drop in charitable giving is m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 57 publications
(71 reference statements)
2
30
0
Order By: Relevance
“…For example, Hrung (2004) finds that giving shifts toward religious causes as people age. That said, other studies which focus on total charitable giving have found agerelated decreases that are qualitatively similar to the ones in our data (Wiepking and James, 2012).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…For example, Hrung (2004) finds that giving shifts toward religious causes as people age. That said, other studies which focus on total charitable giving have found agerelated decreases that are qualitatively similar to the ones in our data (Wiepking and James, 2012).…”
Section: Discussionsupporting
confidence: 92%
“…Illness can also affect people's cognitive abilities, a potentially important consideration given the evidence in the psychology literature of a positive relationship between cognitive skills and the ability to empathize with other people (Wiepking and James, 2012, p. 6). Wiepking and James (2012) examine these various explanations for the decline in giving among the very old in a regression framework using data from the Health and Retirement Study.…”
Section: Introductionmentioning
confidence: 99%
“…People of older age are typically more generous donors. The main reason for this trend is the life cycle effect: older people typically have more financial resources, accumulated over their life (Wiepking & James, 2013). Havens and Schervish (2003) argue that the nonprofit sectors of Western societies can expect an influx of donations with the large 'baby boomer' cohort (born between 1946 and 1955) reaching pensioning age.…”
Section: Population Changesmentioning
confidence: 99%
“…Broadly speaking, donors are more likely to be female, older, married, religious, educated, and wealthy (Bègue, 2014;Bekkers & Wiepking, 2011c;Brooks, 2003b;Choi & DiNitto, 2012;Forbes & Zampelli, 2013;Helms & Thornton, 2012;Herzog & Yang, 2018;Hughes & Luksetich, 2008;Korndörfer, Egloff, & Schmukle, 2015;Leslie, Snyder, & Glomb, 2013;Manesi, Van Lange, Van Doesum, & Pollet, 2018;McGregor-Lowndes & Crittall, 2014;Mesch, Brown, Moore, & Hayat, 2011;Mesch, Osili, Ackerman, & Dale, 2015a;Mesch, Rooney, Steinberg, & Denton, 2006;Midlarsky & Hannah, 1989;Neumayr & Handy, 2017;Rajan, Pink, & Dow, 2009;Rooney, Mesch, Chin, & Steinberg, 2005;Sibley & Bulbulia, 2015;Stavrova & Siegers, 2014;L. Steinberg & Monahan, 2007;Tremblay-Boire & Prakash, 2017;Vaidyanathan, Hill, & Smith, 2011;Wiepking & Bekkers, 2012;Wiepking, Bekkers, & Osili, 2014;Wiepking & James, 2013;Wiepking & Maas, 2009).…”
Section: Who Gives To Charity?mentioning
confidence: 99%
“…Age. As people age, they are more likely to give to charity (Bègue, 2014;Bekkers & Wiepking, 2011c;Herzog & Yang, 2018;McGregor-Lowndes & Crittall, 2014;Mesch et al, 2006;Midlarsky & Hannah, 1989;Neumayr & Handy, 2017;Rajan et al, 2009;Sibley & Bulbulia, 2015;Wiepking & James, 2013), though age is not always a significant predictor of being a donor (Tremblay-Boire & Prakash, 2017). In addition, research has found both that older donors give more on average (Bennett, 2003; and that younger donors do (Midlarsky & Hannah, 1989, Study 1).…”
Section: Demographicsmentioning
confidence: 99%